Community Readiness and Support for Success in Relocating to the New Capital City - Fath, Zain Fuadi Muhammad Roziqi; Kurniawan, Riza Yonisa; Ummah, Safira Nashirothul Nur; Dewi, Retno Mustika; Majid, Mohamad Zuber Bin Abd (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2025)
The capital city functions as a hub for government and commerce. Moving Indonesia’s capital is expected to minimize the economic gap between Java and other regions while addressing Jakarta's increasing unfitness due to overcrowding, environmental decline, and low living standards. Nonetheless, society's readiness is still an essential concern. This research employed an explanatory method with a retrospective design to investigate how individuals' behaviors, which are influenced by their readiness and support for IKN as an eco-friendly capital, shaped their expectations of IKN as a sustainable city. Our findings underscore the urgency of the situation. The current environmental behaviors of the Indonesian people may not be sufficient for realizing a green city. Immediate action is needed to address this. To succeed, the IKN needs better infrastructure, enhanced public transportation, improved walking pathways, and lifestyle changes that encourage sustainability, like using renewable energy and reducing CO2 emissions.